Expanding scope for gender integration and impact: moving beyond individual empowerment to institutional empowerment - Macharia, Kenneth (African Women in Agricultural Research and Development, 2019)
Presented by Kenneth Macharia (AWARD), as part of the Annual Scientific Conference hosted by the University of Canberra and co-sponsored by the University of Canberra, the Australian Centre for International Agricultural Research (ACIAR) and CGIAR Collaborative Platform for Gender Research, Canberra, Australia, April 2-4, 2019.